Electro-Electronic Project of an Articulated Electric Vehicle (Global Journals of Research in Engineering, 2020)
In this work, we present the electro-electronic project of an articulated electric vehicle developed, initially for a user, with electric steering and an articulated center that allows the vehicle and user to enter elevators. The purpose is to allow older adults or people with special needs to obtain greater mobility and comfort on urban and residential roads. The main part of the electronic system is a complete bridge inverter controlled by a microcontroller system. The vehicle features two battery banks, monitored by a control system that defines the best bank to be used, placing the other bank under load through a solar panel. The mechanical structure was constructed from materials that are easily accessible on the market, and materials for reuse to recycle them.
Keywords: electric vehicle; power inverter; special needs